Discover the road sequences of bus lines using bus stop information and historical bus locations - Zhou, Ying (2019)
Discovering the road sequences traveled by the bus lines is of great importance for public transport management, such as bus journey time prediction and multimodal travel route recommendation, as the road sequence provides important information on roadway characteristics such as the number of intersections and traffic signals, road type, and number of lanes. This article develops methods to discover the covered road sequence for a given bus line, using bus stop information as well as historical bus locations (i.e. locations where buses had appeared in history). To solve the problem, we first construct a high-quality global positioning system (GPS) trajectory and then employ a novel map-matching algorithm to the resultant dense trajectory to obtain the road sequence of the bus line. We focus on constructing high-quality trajectory with dense GPS points by (1) forming an initial bus stop trajectory using ordered bus stop coordinates, (2) identifying sufficient suitable historical bus locations, and (3) inserting the identified bus locations into proper positions of the bus stop trajectory. Our proposed method is evaluated on real-world bus line data involving more than 400 bus services in Singapore.